2014
DOI: 10.1002/2014jb011079
|View full text |Cite
|
Sign up to set email alerts
|

The effects of thermomechanical heterogeneities in island arc crust on time‐dependent preeruptive stresses and the failure of an andesitic reservoir

Abstract: Using ground deformation data from Soufrière Hills volcano (SHV), we present results from numerical modeling of the temperature‐ and time‐dependent stress evolution in a mechanically heterogeneous crust prior to reservoir failure and renewed eruptive activity. The best fit models do not allow us to discriminate between a magmatic plumbing system consisting of either a single vertically elongated reservoir or a series of stacked reservoirs. A prolate reservoir geometry with volumes between 50 and 100 km3, reser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(63 citation statements)
references
References 51 publications
(91 reference statements)
2
53
0
Order By: Relevance
“…External triggers represent a source of unpredictability of potential eruptions and are not considered here. At Corbetti, there is no evidence of an eruption in recent decades, or major form of reservoir failure, meaning that the reservoir must be large and/or compressible enough to accommodate the strain associated with the intruding magma (Degruyter et al, ; Gottsmann & Odbert, ). External evidence for a large (∼10 2 km 3 ) magma reservoir comes from the MT observations and the high degree of fractionation required to produce the peralkaline, aphyric erupted products.…”
Section: Discussionmentioning
confidence: 99%
“…External triggers represent a source of unpredictability of potential eruptions and are not considered here. At Corbetti, there is no evidence of an eruption in recent decades, or major form of reservoir failure, meaning that the reservoir must be large and/or compressible enough to accommodate the strain associated with the intruding magma (Degruyter et al, ; Gottsmann & Odbert, ). External evidence for a large (∼10 2 km 3 ) magma reservoir comes from the MT observations and the high degree of fractionation required to produce the peralkaline, aphyric erupted products.…”
Section: Discussionmentioning
confidence: 99%
“…Depth-and temperature-dependent changes of Young's modulus of the crust are ignored for simplicity. We chose a Young's modulus of 30 GPa, representing an average value for crustal rocks in arcs for depths up to 8 km as derived from seismic velocity data (Gottsmann and Odbert, 2014). We test for two typical aquifer types found in volcanic regions: unconsolidated pyroclastic deposits, commonly composed of coarse ash to fine lapilli sized clasts, and Table 3 Water compressibility χ f 4 × 10 −10 Pa −1 changed acc.…”
Section: Model Set-upmentioning
confidence: 99%
“…Loading stresses caused by ice (Pinel et al, 2007) and lava flows (Grapenthin et al, 2010) via long-term (decades), sub-crustal viscous flow have been modelled to explain deformation measured in Iceland, where the elastic crust is comparably thin. Models of ground deformation due to surface loading by a relatively small (few million cubic metres) volume of erupted lava at Merapi volcano suggested that displacements observed outside the crater were not significantly affected (Beauducel et al, 2000).…”
Section: Introductionmentioning
confidence: 99%